Bioinspired hierarchical 3D flower-in-ridge hybrid structure for the photodegradation of persistent organic pollutants. Issue 22 (26th May 2022) - Osotsi, Maurice I.; Xiong, Yuqin; Fu, Siqi; Zhang, Wang; Di, Zhang
Abstract : Next-generation photocatalysts are continuously inspired by natural nanostructures to enhance their characteristics, harness the inherent natural structure properties and boost the photocatalytic performance for efficient degradation of persistent organic pollutants (POPs). Abstract : The development of next-generation photocatalysts has consistently gained inspiration from the evolution of natural nanostructures regarding their fabrication and application for the elimination of persistent organic pollutants (POPs). Herein, we synthesized blue-colored oxygen-vacant Bi2 WO6− x inside butterfly wing architectures (BW-Bi2 WO6− x ) via modified functionalization and solvothermal techniques. Given that the (WO4 ) 2− layer in Bi2 WO6 structurally resembles the structure of WO3, the introduction of oxygen vacancies (OVs) boosts the solar light absorption in comparison to the short visible light absorption range (<450 nm) in pristine Bi2 WO6 (P-Bi2 WO6 ). Hence, the fabricated BW-Bi2 WO6− x sample exhibited broadened photo-absorption over the visible to NIR wavelength range, improved semiconductor attachment on the wing architecture and heightened surface area with numerous active sites for the adsorption of POP molecules. The performance of the BW-Bi2 WO6− x photocatalyst was monitored for the elimination of methylene blue (MB), rhodamine B (RhB) and 4-chlorophenol (4-CP) under UV light exposure, yielding 91%, 92% and 94% degradation, respectively, in 60 min. Similarly, the degradation efficiencies of 94%, 98% and 98% for the photodegradation of MB, RhB and 4-CP under visible light for 60 min, respectively, were observed. Under NIR light, 80%, 79% and 85% degradation efficiencies were observed for MB, RhB and 4-CP, respectively, after 60 min. Therefore, the proposed BW-Bi2 WO6− x sample can provide insights and inspire the development of photo-responsive materials for applications in energy, defense and water treatment.